Reprogramming the Epigenome With Vitamin C - Lee Chong, Taylor; Ahearn, Emily L.; Cimmino, Luisa (Frontiers in Cell and Developmental Biology, 2019)
The erasure of epigenetic modifications across the genome of somatic cells is an essential requirement during their reprogramming into induced pluripotent stem cells (iPSCs). Vitamin C plays a pivotal role in remodeling the epigenome by enhancing the activity of Jumonji-C domain-containing histone demethylases (JHDMs) and the Ten-eleven translocation proteins (TETs). By maintaining differentiation plasticity in culture, vitamin C also improves the quality of tissue specific stem cells derived from iPSCs that are highly sought after for use in regenerative medicine. The ability of vitamin C to potentiate the activity of histone and DNA demethylating enzymes also has clinical application in the treatment of cancer. Vitamin C deficiency has been widely reported in cancer patients and has recently been shown to accelerate cancer progression in disease models. Therapies involving high-dose vitamin C administration are currently gaining traction in the treatment of epigenetic dysregulation, by targeting aberrant histone and DNA methylation patterns associated with cancer progression.